Heritability of Lung Function in Severe Alpha-1 Antitrypsin Deficiency - DeMeo, D.L.; Campbell, E.J.; Brantly, M.L.; Barker, A.F.; Eden, E.; McElvaney, N.G.; Rennard, S.I.; Stocks, J.M.; Stoller, J.K.; Strange, C.; Turino, G.; Sandhaus, R.A.; et al. (Human heredity, 2009)
Severe alpha-1 antitrypsin (AAT) deficiency is a proven genetic risk factor for COPD, but there is marked variation in the development of COPD among AAT deficient subjects. To investigate familial aggregation of lung function in subjects with AAT deficiency, we estimated heritability for forced expiratory volume in 1 s (FEV 1) and FEV 1/forced vital capacity (FVC) in 378 AAT deficient subjects from 167 families in the AAT Genetic Modifiers Study; all subjects were verified homozygous for the Z AAT deficiency allele. Heritability was evaluated for models that included and excluded an ascertainment correction, as well as for models that excluded, included and were stratified by a cigarette smoking covariate. In models without an ascertainment correction, and in all models without a covariate for smoking, no evidence for familial aggregation of lung function was observed. In models conditioned on the index proband with covariates for smoking, post-bronchodilator FEV 1/FVC demonstrated significant heritability (0.26 ± 0.14, p = 0.03). When we limited the analysis to subjects with a smoking history, post-bronchodilator FEV 1 demonstrated significant heritability (0.47 ± 0.21, p = 0.02). Severity rate phenotypes were also assessed as potential phenotypes for genetic modifier studies. Significant heritability was found with all age-of-onset threshold models that included smoking and ascertainment adjustments. Using the t-distribution, the heritability estimates ranged from 0.43 to 0.64, depending on the ageof-onset of FEV 1 decline used for the severity rate calculation. Correction for ascertainment and consideration of gene-by-smoking interactions will be crucial for the identification of genes that may modify susceptibility for COPD in families with AAT deficiency.